(untitled) (CIPEEX, 2022)
THE RIGHT TO ANIMAL PROTECTION IS A RIGHT SUPPORTED BY LAW AND REPRESENTED BY MAN TO ACHIEVE THE NECESSARY EFFECTS FOR ANIMALS. IN THIS WAY, IT IS THE CIVIL RESPONSIBILITY OF THE STATE, AS WELL AS OF THE TUTORS, AND OF THE NON-TUTORS THAT I TITLED REFERRING TO AN ETHICAL PERSON, IN SUCH A WAY, EVEN IF THEY DO NOT HAVE ANIMALS, THEY ARE AWARE THAT IT IS NECESSARY TO KEEP THEM WITH PROTECTION, PREVENTING THEM FROM BEING ABANDONED OR MISTREATED AS HAPPENS QUITE OFTEN. IT IS NECESSARY TO PROMOTE THE WELFARE OF ANIMALS WITH THE SAFETY THEY DESERVE, LEGAL NORMS AND PRINCIPLES OF ETHICS AND MORALS ARE ESSENTIAL ELEMENTS FOR THE BRANCH OF LAW, THEY CONTRIBUTE BY PROVIDING LAWS AND PROTECTIVE MEASURES THAT ACT WITH PUNISHMENT IN CASES OF VIOLATIONS. OF ANIMAL LAW. THE ARTICLE AIMS TO PROVIDE KNOWLEDGE OF ANIMAL RIGHTS, AND DEMONSTRATE HOW THE HISTORICAL EVOLUTION OF ENVIRONMENTAL LAW HAS ADDED VALUES €‹€‹TO ANIMAL PROTECTION. HOWEVER, THE SUPPORT OF LEGISLATION IS EXTREMELY IMPORTANT FOR THE LEGAL NATURE, ALTHOUGH IT IS A MATTER THAT IS NOT OF PRIMARY INTEREST TO LEGISLATORS, SINCE ANIMAL LAW IS A THING, PUTTING HUMAN LAW IN THE FIRST PLACE, WHICH IS SAID TO BE SOMETHING UNDERSTANDABLE TO SOME EXTENT. THE DEVELOPMENT OF THIS ARTICLE IS NECESSARY SO THAT THE THOUGHT OF PROTECTING ANIMAL RIGHTS IS ALWAYS REFLECTED IN CONSTITUTIONAL VALUES, AT THE PRESENT MOMENT SO THAT FUTURE GENERATIONS FOLLOW THIS EXAMPLE, WITHOUT THE NEED TO FIGHT FOR SOMETHING THAT SHOULD BE IMPOSED WITHOUT SUCH DIFFICULTY, EQUALLY, AS WELL AS THE STRICTEST EXISTING CIVIL LAW LAWS. SO THAT SUSTAINABLE DEVELOPMENT IS PRESERVED AND HOW IMPORTANT THE REPRESENTATION OF NATURE PROTECTION FOR OUR PLANET IS.